1973
DOI: 10.1107/s0567740873007016
|View full text |Cite
|
Sign up to set email alerts
|

The crystal and molecular structure of the diterpenoid baccatin V, a naturally occurring oxetan with a taxane skeleton

Abstract: 2566THE CRYSTAL STRUCTURE OF [Co(NHa)614CusCI17 this diminution in the size of anion would lead to a less stable structure as the cations would then be in contact with each other. In the present compound the empirical formula of the anion [Cux. 25C14.25] leads to a greater effective volume for the anion which will be much nearer to the volume of the [CuC15] 3-ion.The structure shows clearly how twinning can occur since over 60 % of the scattering material (based on f 2) lies on the diagonal (110) plane (x=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…This observation was thought to be due to the strong hydrogen bonding formed between the 7ahydroxyl to the acyl oxygen of the 4a-acetate, first observed in baccatin III crystal structure. 11 However, NMR studies of paclitaxel and other taxanes in solution indicated that some original intramolecular hydrogen bonding could be lost with the concomitant appearance of the new hydrophobic interactions. 14,15 For paclitaxel and its derivatives investigated in this study, their equilibrium constant for epimerization, K, does not show big variance from a range of 0.2 to 1 under most experimental conditions.…”
Section: Influence Of the Substituents On Epimerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation was thought to be due to the strong hydrogen bonding formed between the 7ahydroxyl to the acyl oxygen of the 4a-acetate, first observed in baccatin III crystal structure. 11 However, NMR studies of paclitaxel and other taxanes in solution indicated that some original intramolecular hydrogen bonding could be lost with the concomitant appearance of the new hydrophobic interactions. 14,15 For paclitaxel and its derivatives investigated in this study, their equilibrium constant for epimerization, K, does not show big variance from a range of 0.2 to 1 under most experimental conditions.…”
Section: Influence Of the Substituents On Epimerizationmentioning
confidence: 99%
“…Epimerization of paclitaxel, baccatin III, and various other taxanes during isolation and chemistry studies were noted. [4][5][6][7][8][9][10][11] This paper focuses on the kinetics of the epimerization of paclitaxel and related compounds in aqueous solution. The reaction kinetics was determined under various pH and temperature conditions in an attempt to clarify the mechanism of the epimerization which was previously unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrogen bonding can partially inactivate the 7α‐hydroxyl group leading to the difference in the deprotonation potential of the C7OH between 1a and 1b . Furthermore, previous reports also revealed that the intramolecular hydrogen bonding could partially alter the three‐dimensional (3D) conformation of 7α‐hydroxyltaxanes and make the peripheral part of the C2 benzoyl more exposed 44, 45. Both the altered conformation and the inactive C‐7 α‐OH indicated that C1OH was the most favorable deprotonation site for 1b , which can induce the neutral loss of BzOH from the C‐2 benzoyl.…”
Section: Resultsmentioning
confidence: 94%
“…Ring A, 'double-bridged' to the central ring, exhibits the 1,3-diplanar boat conformation with Cll only 0.36 (1) and C15 0.98 (1)A fully above the mean plane of the atoms C13, C12, C14 and C1 [maximum deviation: 0.01 (1)A]. These conformations are more or less identical for all the baccatin derivatives resolved by Xray analysis: baccatin V (Castellano & Hodder, 1973), O-cinnamoyltaxicin-I triacetate (Begley, Frecknall & Pattenden, 1984), 14/3-hydroxy-10-deacetylbaccatin III (Appendino et al, 1992), N-tert-butoxycarbonyl-lOdeacetyl-N-debenzoyltaxol (Gurritte-Voegelein et al, 1990), 9-dihydro-13-acetyl-baccatin III (Gunawardana et al, 1992).…”
Section: Commentmentioning
confidence: 91%